Ehlers Danlos Syndrome: The Story - Takahashi-Ferrer, Carolina Mayo (2022)
Several authors have made contributions on Ehlers Danlos Syndrome, its beginnings in ancient Greece approximately 400 b.C. During this period, Hippocrates recorded that the Scythian nomads had loose joints and had several scars. Then in 1682 the Amsterdam surgeon Job Von Meekeren made the first description of this syndrome. I have seen that over time the definition and classification of the syndrome has evolved to become a diagnostic entity. The present article aims to summarize the main authors who cooperated with the description and classification of Ehlers Danlos Syndrome.